2020
DOI: 10.1080/10942912.2019.1705336
|View full text |Cite
|
Sign up to set email alerts
|

Induced resistance in peach fruit as treated by Pichia guilliermondii and their possible mechanism

Abstract: This research aims to assess the effect of Pichia guilliermondii treatment on the improved disease resistance of the peach fruit and to explore the biocontrol mechanisms. Infection rate and lesion diameter of the yeasttreated fruit were substantially inhibited after Rhizopus stolonifer and Penicillium expansum infection, respectively. A significant increase in endogenous salicylic acid (SA) content was stimulated in peach fruit treated with P. guilliermondii. The activities of defense-related enzymes and the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The impact of BTHWA on the development of Rhizopus stolonifer was also considered within the experiment performed, but as the level of attack of this pathogen was very low in general, it was difficult to establish significant differences. The information on the positive effect of SAR mechanism on the infection with Rhizopus stolonifer has been reported by Zhao et al [62].…”
Section: Discussionmentioning
confidence: 93%
“…The impact of BTHWA on the development of Rhizopus stolonifer was also considered within the experiment performed, but as the level of attack of this pathogen was very low in general, it was difficult to establish significant differences. The information on the positive effect of SAR mechanism on the infection with Rhizopus stolonifer has been reported by Zhao et al [62].…”
Section: Discussionmentioning
confidence: 93%
“…While studies indicate that their biocontrol efficiency may be increased, limited studies examine the combined effect on the antimycotoxigenic characteristics of yeasts. There are several studies combining agents, such as β-glucan, , phytic acid, methyl jasmonate, , melatonin, N -acetylglucosamine, γ-aminobutyric acid, cinnamic acid, glycine betaine, ,, chitosan, , calcium chloride, and arginine . Apart from the combination with an agent, the impact of different processes on the efficiency of the antagonistic yeast was also investigated, including hot air, microwave, UV-C irradiation, and heat shock .…”
Section: Combined Application Of Antagonistic Yeasts For Enhanced Bio...mentioning
confidence: 99%
“…Among these various mechanisms, the induction of host resistance is especially intriguing. Studies have shown that antagonistic yeasts can increase resistance-related enzyme activity [such as β-1,3-glucanase, phenylalanine ammonia-lyase, peroxidase, (POD), and polyphenol oxidase (PPO)] in fruit, and the expression of stress resistance genes that have been associated with enhanced resistance to biotic and abiotic stress [8] , [9] . Therefore, a comprehensive understanding of the mechanisms underlying the ability of an antagonistic yeast to prevent postharvest infections and maintain quality can provide information that can be used to apply this technology in an efficient and effective manner.…”
Section: Introductionmentioning
confidence: 99%